Green Management as The Key to Competitive Advantage: A Corporate Strategy Perspective in 2024 - Azhari, Azlan; Rahmat, Muh. Rijal Alim; Ridha, Achmad (PT. Maju Malaqbi Makkarana, 2024)
Green management has become a crucial element in modern corporate strategies to achieve competitive advantage while supporting environmental sustainability. This study analyzes the implementation of five key segments of green management: greening of products, processes, workplaces, communities, and workforce. Case studies of global companies such as Samsung, Patagonia, and IKEA demonstrate that integrating green strategies not only reduces environmental impact but also enhances operational efficiency, innovation, and customer loyalty. The findings affirm that green management is a strategic investment that yields long-term benefits, particularly in attracting sustainability-focused investors. The study concludes by emphasizing the importance of synergy between the private sector, government, and society in achieving inclusive economic growth aligned with the Sustainable Development Goals